ANALYSIS OF ENGLISH SYNTACTIC STRUCTURE OF COORDINATION IN"COVER STORY" COLUMN ARTICLES IN CAMPUS ASIA MAGAZINE - OCTAVIANI, SALY KURNIA (2011)
The study aims at describing the distributions of English syntactic structure of coordination and identifying the categories being coordinated in the Cover Story column articles in Campus Asia magazine based on syntactic structural approach. The object of the study is sentences having English syntactic structure of coordination in Cover Story column articles of Campus Asia Magazine. The method of data collection is documentation. The study is descriptive qualitative. The technique of analyzing data is based on structural grammar approach. It means that the researcher analyzes the data in the sentences having syntactic structure of coordination with using Chinese box. The findings show that (1) there are four kinds of distributions of syntactic structure of coordination based on its functions in sentence; subject, predicate, object, and complement. While there are two kinds of distributions specifically based on its functions in phrases; head and modifier. (2) the categories being coordinated are divided into three; clause which appears in independent clause and dependent clause; phrase which appears in noun phrases, verb phrases, infinitive phrases, prepositional phrases, and prepositional gerund phrases; and words which appears in noun, verb, adjective and adverb.